The Reason’s Structure of Moslem Sculptor In Prumpung Magelang; Analysis Of The Hadith About The Prohibition Of Statues Through Umberto Eco’s Semiotic-Communication Model - Ahmad Mustofa (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2021)
Normatively, the existence of a statue has been agreed upon as forbidden in Islam. The argument for the prohibition of its existence can also be found in various textual traditions, so that among Muslim scholars and intellectuals, there are almost no rejection regarding the prohibition. Therefore, the objects of art that are accommodated in Islamic traditions are limited to inanimate objects such as flowers and plants, which then give bring up to distinctive ornamental arts in the Islamic tradition. However, in the Prumpung Magelang area, there is a center for the andesite sculpture industry, with the majority of the carvers being devout Muslims. The gap that arises between the doctrine of the prohibition of statues on the one hand, and the existence of Muslim sculptors on the other is the main theme discussed in this study. Meanwhile, the approach used in this study uses the semiotic-communication concept initiated by Umberto Eco. The study concludes that the existence of statues according to the sculptors in Prumpung Magelang does not have theological problems as the doctrine understood by the majority of Muslims, therefore the profession as a sculptor for them is a lawful profession like other professions.